Precocious Puberty: Experience of 48 Cases - Valdivia, Freddy (1997)
Forty eight children with precocious puberty were evaluated from May 1988 to December 1996 in the Department of Endocrinology, Hospital Nacional Guillermo Almenara Irigoyen. Forty seven patients (97,9%) had central precocious puberty (CPP) and 1 (2,1%) had periferic precocious puberty (PPP). Among children with CPP, 87,23% were female and 12,77% male. Male patients had an earlier beginning of puberty, a major delay in first attendance and a major bone age/chronological age ratio. 92,7% of female and 33,3% of male patients had no associated pathology to CPP. GnRH test was the most useful test for diagnosis, and imaging studies (CT scan and MRI) were important for male patients. Only one patient had PPP, he was a male with Leydig cell tumor.